Peer assessment practices in an online context: does the group size matter? - Chiara Pelati; Valentina Grion; Lan Li; Anna Serbati (Firenze University Press, 2020)
The present study examined how group size may impact students' participation, perceptions, and work quality in an online peer assessment activity. One hundred sixty-three college freshmen were randomly assigned into three conditions that consisted of either 3-student groups, 6-student groups, or 9-student groups. Students reviewed each other's projects within their groups. Upon receiving peer feedback, students improved their own work. The data analysis suggested that students in bigger groups more actively participated in peer review discussion than students in smaller groups. For students' perceptions, students' responses to SCS and IMI questionnaires did not show considerable differences between the three groups. For work quality, it seemed that students in bigger groups outperformed students in smaller groups.   Pratiche di valutazione fra pari in un contesto on line: quale impatto ha la numerosità del gruppo? Il presente lavoro considera l'impatto della numerosità del gruppo su partecipazione, percezioni e qualità del lavoro degli studenti in attività on line di valutazione fra pari. 163 matricole sono state distribuite, in modo casuale, in gruppi di lavoro da tre, da sei o da nove studenti. Essi hanno esaminato i prodotti dei pari all'interno del proprio gruppo. Dopo aver ricevuto feedback dai pari, gli studenti hanno migliorato il proprio lavoro. L'analisi dei dati ha permesso di rilevare che gli studenti di gruppi più numerosi partecipano più attivamente alla discussione di peer review, rispetto a quelli di gruppi meno numerosi. Non vi sono, invece, differenze significative di risposta ai questionari SCS e IMI. Considerando la qualità del lavoro, si è constatato che gli studenti di gruppi più numerosi ottengono prodotti migliori di quelli di gruppi meno numerosi.